The impact of joint participation on liquidity in equity and syndicated bank loan markets - Allen, Linda; Gottesman, Aron A.; Peng, Lin (Journal of Financial Intermediation, 2012)
Market liquidity is impacted by the presence of financial intermediaries that are informed and active participants in both the equity and the syndicated bank loan markets, specifically informationally advantaged lead arrangers of syndicated bank loans that simultaneously act as equity market makers (dual market makers). Employing a two-stage procedure with instrumental variables, we identify the simultaneous equations model of liquidity and dual market maker decisions. We find that the presence of dual market makers improves the liquidity of the more competitive and transparent equity markets, but widens the spread in the less competitive over-the-counter loan market, particularly for small, informationally opaque firms.